Efektivitas Konsentrasi dan Frekuensi Pemberian Urin Sapi Segar Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) - Rifai La Ipa; Anthony Walsen; Jeane I Nendissa (Fakultas Pertanian, Universitas Pattimura, 2021)
This study aims to find out the effectiveness of the concentration and frequency of fresh cow urine application both singly and in interactions on the growth and production of shallots (Allium ascalonicum L), conducted from November 2020 to January 2021 in the greenhouse of the Faculty of Agriculture, Pattimura University, Ambon. This study used a factorial completely randomized block design with 2 treatment factors. The first factor was the concentration of fresh cow urine with four levels: KO (Control), K1 (10% urine concentration), K2 (20% urine concentration), and K3 (30% urine concentration), while the second factor was the frequency of application with three levels, namely: F1 (2 MST), F2 (4 MST), F3 (6 MST). Parameters observed were number of leaves, leaf area, plant length, number of tubers, fresh weight of tubers, fresh weight of leaves, dry weight of tubers, total plant dry weight, net assimilation rate, plant growth rate and harvest index. The results of the study showed that the concentration and frequency of its application and their interactions were not effective on all variables of growth and production of shallot plants but had a good tendency on several variables including the number of leaves (4 MST and 6 MST), plant length (2 MST and 6 MST) and total dry weight of plants after treatment of 20% cow urine concentration given 3 times, at 2 MST and 6 MST.